Kidney transplantation in patients with severe preoperative hypertension. (20th July 2015) - Ajaimy, Maria; Lubetzky, Michelle; Kamal, Layla; Gupta, Anjali; Dunn, Colin; de Boccardo, Graciela; Akalin, Enver; Kayler, Liise
Abstract: Background: Severe systemic hypertension (HTN) is a risk factor for perioperative cardiovascular complications; however, its impact at the time of kidney transplantation (KTX) is not well defined. Methods: A retrospective cohort study of adult kidney‐only transplant recipients between October 2009 and December 2012 was performed to examine outcomes between patients with (n = 111) and without (n = 98) severe preoperative HTN defined as SBP >180 or DBP> 110 mmHg. Results: Recipients with severe HTN were older (56.7 ± 13.0 vs. 53.5 ± 12.4 yr, p = 0.07) and significantly more likely to receive an expanded criteria donor kidney (32.7% vs. 12.2%, p = 0.02). No patients developed hypertensive crisis, intracranial hemorrhage, or life threatening ventricular arrhythmias within 30 d post‐transplantation; however, three patients with severe HTN had cardiac events: two with demand ischemia and one with decompensate heart failure. Two patients in the control group had decompensated heart failure. There were no differences between the groups in terms of cardiac event (2.7% vs. 2.0%, p = 0.75), one‐yr patient survival (98.2% vs. 98.0%, p = 0.90) or graft survival (90.1% vs. 92.9%, p = 0.48), nadir creatinine >2 mg/dL (4.6% vs. 6.2%, p = 0.62), length of stay>6 d (37.8% vs. 35.7%, p = 0.75), and DGF (52.3% vs. 63.3%, p = 0.11). Conclusions: Our results suggest that severe preoperative HTN should not be considered an absolute contraindication to kidney transplant in patients who are otherwise clinically stable.